The Impact Of Climate Change On The Increase Of Flood And Landslide Disaster In Kuningan Regency, West Java Province - Salsa Firdausiah’adah; Adi Subiyanto; Ali Rahmat; Pujo Widodo; Herlina Juni Risma Saragih (CV. AFDIFAL MAJU BERKAH, 2023)
Kuningan Regency, which is one of the areas that prone to landslides and floods. Based on its geological and geographical conditions, Kuningan Regency is located on the slopes of Mount Ciremai so that this area has a high level of vulnerability to landslides and floods. This study aims to identify climate change with rainfall indicators that have an impact on increasing the incidence of floods and landslides in Kuningan Regency as well as disaster risk reduction efforts by the Regional Disaster Management Agency (RDMA) and the local community. This study uses a qualitative method with a descriptive approach, supported by data obtained from observations, interviews and literature studies. The results showed that climate change with high rainfall indicators had an effect on an increase in landslides and floods that occurred in Kuningan Regency. Disaster risk reduction efforts from the Kuningan Regency BPBD in tackling the risks of floods and landslides, namely by taking preventive action. RDMA Kuningan Regency has built public facilities such as shelter for refugees, signs for evacuation routes, early warning system, as well as strengthening disaster risk reduction forums in Kuningan District. The efforts that can be made by the community are by carrying out repairs, cleaning waterways, building cliff retaining walls and closing soil cracks